Electroanalysis with carbon paste electrodes - Svancara, Ivan (Analytical chemistry series, 2012)
With an emphasis on practical applications, Electroanalysis with Carbon Paste Electrodes provides a comprehensive overview of carbon paste electrodes. The text offers a comprehensive and unprecedentedly wide insight into the realm of the carbon paste material, culminating with a systematic presentation of all the methods and procedures applicable to the determination of a myriad of inorganic and organic substances when employing the individual types and variants of carbon paste-based electrodes, sensors, and detectors.